2007
DOI: 10.1021/jp0710180
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Intrinsic Conductivity of Novel Pyrrole Copolymer Nanoparticles with Inherent Self-Stability

Abstract: Intrinsically self-stabilized nanoparticles of a copolymer from 4-sulfonic diphenylamine (SD) and pyrrole (PY) were facilely synthesized in HCl solution at 10 degrees C by a chemically oxidative polymerization. The critical reaction parameters such as SD/PY ratio, polymerization time, and oxidant species were studied to significantly optimize the polymerization yield, size, conductivity, and solubility of the final copolymer particles. The molecular structure, size, size distribution, and morphology of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 34 publications
0
51
3
Order By: Relevance
“…4e). While PPy nanoparticles demonstrated that stretching bands at 1472 and 1550 cm À1 due to the pyrrole ring [27], a shoulder band at 1690 cm À1 assigned to part of the oxidized pyrrole ring [28], two bands at 1032 and 1301 cm À1 attributed to CÀN stretching bands [29], and stretching bands at 923 and 1202 cm À1 generated by doped PPy [30]. Note that a small shoulder band at 740 cm À1 appeared in spectra of PPy nanoparticles, indicating that a small amount of 2,4-diaminodiphenylamine has copolymerized with pyrrole, as shown in Scheme 1.…”
Section: Ft-ir Spectramentioning
confidence: 99%
“…4e). While PPy nanoparticles demonstrated that stretching bands at 1472 and 1550 cm À1 due to the pyrrole ring [27], a shoulder band at 1690 cm À1 assigned to part of the oxidized pyrrole ring [28], two bands at 1032 and 1301 cm À1 attributed to CÀN stretching bands [29], and stretching bands at 923 and 1202 cm À1 generated by doped PPy [30]. Note that a small shoulder band at 740 cm À1 appeared in spectra of PPy nanoparticles, indicating that a small amount of 2,4-diaminodiphenylamine has copolymerized with pyrrole, as shown in Scheme 1.…”
Section: Ft-ir Spectramentioning
confidence: 99%
“…The IR spectrum of polypyrrole exhibits well-defi ned peaks that are characteristic of this polymer (see Table S1). [39][40][41][42] In contrast, the carbonized and activated samples exhibit broader and overlapping bands due to the strong absorption of carbon. All the spectra exhibit a peak that is characteristic of C = C stretching vibrations in aromatic rings at ≈ 1590 cm − 1 for the carbonized sample and 1590-1620 cm − 1 for the activated samples.…”
Section: Chemical Properties Of N-doped Activated Carbonsmentioning
confidence: 99%
“…Polypyrrole (PPy) is a commonly used conducting polymer due to its good stability, ease of synthesis, and greater conductivity compared to other conductive polymers [32]. It is used for a wide range of biological applications due to its ability to support growth of electrically responsive cells such as neuronal cells [33], bone cells, and smooth muscle cells [34].…”
Section: Electric and Magnetic Field-responsive Polymersmentioning
confidence: 99%
“…It is used for a wide range of biological applications due to its ability to support growth of electrically responsive cells such as neuronal cells [33], bone cells, and smooth muscle cells [34]. Li et al [32] had synthesized stable, conductive NPs using a copolymer of PPy and 4-sulfonic diphenylamine (SD). The NPs having 50/50 monomer ratio showed the smallest size (20 nm) and highest conductivity (0.217 S cm À1 ) when using FeCl 3 as an oxidant during synthesis.…”
Section: Electric and Magnetic Field-responsive Polymersmentioning
confidence: 99%